Evolutionary Origin and Genetic Diversity of the Pannonian Ecotype of Apis mellifera carnica Colonies in Hungary Based on Mitochondrial DNA and Microsatellite Markers - Reka Balazs; Tamas Gergely Molnar; Erika Edvine Meleg; Andras Hidas; Edit Zajacz; Timea Racz; Nora Palinkas-Bodzsar (Biology)
Honey bees are crucial to both the ecosystem and the economy. However, they are subject to different influences that can lead to a loss of genetic diversity. In this study, we used mitochondrial DNA information and nuclear microsatellite markers to compare worker individuals that strictly meet the morphological breed standard of the Pannonian bee in Hungary to those with morphological disorders (yellow color of the abdomen). Additionally, this study involves Carniolan colonies from two European countries and other bee subspecies as a reference group that might have crossed into the Pannonian bee. As for the mitochondrial DNA, the combined assessment of COI and 16S genes identified six haplotypes. Based on the tRNAleu-cox2 intergenic region (E2/H2), our samples belonged to the C evolutionary lineage. According to the microsatellite data, the level of inbreeding was low in all groups investigated, and only the genotypes of the Pannonian bee showed significant deviation from the Hardy–Weinberg equilibrium state. Cluster analysis and the Discriminant Analysis of Principal Components showed that bees that failed the morphological breed identification had started to diverge genetically from those meeting the breed standards, becoming more similar to the Carniolan bee. Our findings suggest that the genetic status of the Pannonian bees investigated in this study is satisfactory. However, in order to maintain an adequate level of diversity, periodic genetic monitoring of the colonies is necessary.